Applications of Raman spectroscopy in the development of cell therapies: state of the art and future perspectives. Issue 6 (19th February 2020) - Rangan, Shreyas; Schulze, H. Georg; Vardaki, Martha Z.; Blades, Michael W.; Piret, James M.; Turner, Robin F. B.
Abstract : This comprehensive review article discusses current and future perspectives of Raman spectroscopy-based analyses of cell therapy processes and products. Abstract : Therapies based on injecting living cells into patients offer a huge potential to cure many degenerative and deadly diseases, with hundreds of clinical trials ongoing. Due to their complex nature, a basic understanding of their biochemical and functional characteristics, how to manufacture them for safe and efficacious therapy, and how to effectively implement them in clinical settings are very challenging. Raman spectroscopy could provide an information-rich, non-invasive, non-destructive analytical method to complement the use of conventional sample-based, infrequent and destructive biochemical assays typically employed to analyze and validate the quality of therapeutic cells. This article provides an overview of the current state of emerging cell therapies, and then reviews the related Raman spectroscopic state of the art analysis of human cells. This includes spectroscopic data processing considerations, the scope offered by technical variants of Raman spectroscopy, and analytical difficulties encountered by spectroscopists working with therapeutic cells. Finally, we outline a number of salient challenges as cell therapy products are translated from the laboratory to the clinic, and propose how Raman spectroscopy-based solutions could address these challenges.